Association between DRD2/DRD4 interaction and conduct disorder: A potential developmental pathway to alcohol dependence. Issue 6 (2nd July 2013) - Mota, Nina R.; Bau, Claiton H. D.; Banaschewski, Tobias; Buitelaar, Jan K.; Ebstein, Richard P.; Franke, Barbara; Gill, Michael; Kuntsi, Jonna; Manor, Iris; Miranda, Ana; Mulas, Fernando; Oades, Robert D.; et al.
<x xml:space="preserve">Abstract</x> © 2013 Wiley Periodicals, Inc.